EXPRESSION OF ERGOTOPE-ASSOCIATED MARKERS BY ACTIVATED T-LYMPHOCYTES - O. Yu. Korol’kova; V. V. Senyukov; V. S. Kozhevnikov (Медицинская иммунология, 2014)
Abstract. Anti-ergotypic response is considered to contribute significantly to the regulation of immune response. Ergotope-associated antigenic determinants include molecules upregulated on the surface of activated T cells (CD25, hsp60 and others). Anti-ergotypic cells are directed against these surface determinants usually complexed to MHC-I and/or MHC-II. Here we demonstrate regulated expression of HLA-Dr, СD25, hsp60 and hTERT mRNA during in vitro activation of peripheral T-lymphocytes with anti-CD3 antibodies and IL - 2, with reactivation on day 7. The percentage of CD25-expressing T cells showed sharp increase as early, as by the day 3 of activation, and it varied only slightly at later terms. The hsp60 levels rose as well, reached a peak at day 3, and gradually decreased thereafter. HLA-Dr expression was induced upon the activation, with a peak at the days 8 or 10. hTERT mRNA amounts also increased, as compared with baseline values, showing two peaks at the days 3 and 8. Anti-ergotopic response may control autoimmunity by targeting the activated T cells, regardless of their specificity. Therefore, immunotherapy of different autoimmune disorders aiming to activate anti-ergotopic responses, may be of a sufficient clinical interest.